Novel open-WDM technical architecture for 5G fronthaul network - Dong WANG; Han LI; Dechao ZHANG; Qian CAI; Jiang SUN; Yang ZHAO; Yunbo LI; Liuyan HAN (Dianxin kexue)
C-RAN may be a promising way for 5G fronthaul network associated with significant changes in 5G fronthaul architecture.Based on the analysis of existing schemes such as optical fiber direct connection,passive WDM and active WDM/OTN,open wavelength division multiplexing (open-WDM) system was proposed to satisfy the new requirements of 5G fronthaul network.In the open-WDM system,WDM technology is used to save optical fiber resource and the semi-active architecture can achieve flexible deployment.The low-cost management and control technology was further applied to perform efficiently network operation.